Pengelompokan Jumlah Kasus Penyakit Aids Berdasarkan Provinsi Menggunakan Metode K-Means - Rut Indra Lita Sinaga; Widodo Saputra; Hendry Qurniawan (LPPM STIKOM Tunas Bangsa, 2021)
Acquired Immune Deficiency Syndrome (AIDS) is a collection of symptoms due to a gradual decline in the immune system caused by infection with the Human Immunodeficiency Virus (HIV). This disease is a dangerous disease and should be watched out for where it spreads very quickly. AIDS is one of the top infectious diseases that can cause death. K-Means is an algorithm in data mining that can be used to group / cluster data. There are many approaches to creating clusters, one of which is to create rules that dictate membership in the same group based on the level of equality among its members. The purpose of this study was to classify the number of AIDS cases by province. To solve the existing problems, the authors will use the K-Means cluster method using 2 clusters to determine the province which has the highest cases of AIDS and the province with the lowest cases of AIDS by calculating the centroid / average of the data in the cluster. It is especially recommended that the government take advantage of the results of this research to pay more attention and make efforts in overcoming AIDS in provinces with high AIDS disease.